Students’ Awareness of Career Counseling - Abudova, Aysel; Mamishova, Gulara; Alizada, Surayya; Huseynova, Tovus; Rasulova, Zulfiyya (ADA University, 2025)
This study aims to explore upper secondary private school students’ perceptions of career counseling and to examine the extent to which these services support their career decision-making processes in the context of Azerbaijan. Drawing on a growing body of international research that emphasizes the value of early and comprehensive career guidance (Cohen-Scali et al., 2018; Weber et al., 2017), this study responds to a notable gap in the local literature, where student perspectives on career counseling remain largely underexplored (European Training Foundation, 2022; Namazova, 2023). Adopting an exploratory qualitative approach, data were collected through semistructured interviews with current students, a graduate, and a career counselor at a private school in Baku. The findings suggest that while students are generally aware of career counseling services, their understanding is often limited and primarily focused on university admission. The timing of counseling interventions, parental influence, and resource constraints within schools emerged as significant factors affecting student engagement and perceived relevance (Sharapova et al., 2023; Zahra & Malik, 2024) This research culminates in a set of practical, evidence-based guidelines intended to inform private schools and educational policymakers on enhancing the delivery of career counseling services. These recommendations promote earlier, more personalized, and diversified career guidance models to better align with students’ evolving needs. A key limitation of this study is the restricted sample size, which, while allowing for in-depth inquiry, limits the generalizability of the findings (Creswell & Poth, 2018)
Keywords: High school students -- Attitudes -- Azerbaijan; Vocational guidance -- Azerbaijan; Education, Secondary -- Private schools; Education, Secondary -- Private schools; Education